Traffic light anti violation system - Obay Ishtayyah; Tayseer Halaweh (My University, 2011)
The idea of ourproject comes from  reality in which we live where there is a lot of accidents that occur on the roads as a result of crossing the red signal in addition to traffic jams, which our  city suffering  from it  .Also to provide security and reduce the effort of many people and these problems claim the lives of many human and material losses. From here came the idea of our project comes from. This project based on different subsystems contains induction loop connected with  microcontroller cheek  the violation   and mobile connected with microcontroller via Bluetooth to take picture from the violator and send it to the server and program on PC to edit  this traffic violation ,during this process we use  mobile network to upload pictures from mobile and download pictures from the server to the PC . This program can be used in police stations to identify the traffic violation without the need for a policeman at this junction and uncover the reasons for the accidents that occur on the roads and find out the reasons the writing or performing of this offense based on the existence of data specific to each driver, such as car number and the name of the violator after this process.Where they can write of the offense and sent to the person without the need for a violator or police officer. And also use this system in the municipalities to handle traffic problems and avoid traffic jams